Challenges in the miRNA research. (1st January 2013) - Singh, Tiratha Raj; Gupta, Arun; Suravajhala, Prashanth
While it is known that the human genes are regulated by microRNAs (miRNAs), recent links with cancer and other diseases have widely caught interest. With several bioinformatics platforms and approaches on rise that has led to discovery of human miRNAs, validation and need for understanding miRNAs from their progenitor messenger RNAs (mRNAs) have arisen. Furthermore, the miRNAs are known to have synergism involving regulation of their condition-specific target genes (mRNAs). In this review, we provide a bioinformatics approach of the miRNAs and their challenges with respect to annotation. With introduction of sequence-specific miRNA signatures recently found, we discussed myriad of dimensions where miRNAs are being associated with several putative functional and evolutionary events, and then we asked a question how far and relevant is the association of miRNAs with mRNAs?